A Comprehensive Study of the Relationship between the Production of β-Lactamase Enzymes and Iron/Siderophore Uptake Regulatory Genes in Clinical Isolates of Acinetobacter baumannii - Mahyar Porbaran; Hamed Tahmasebi; MohammadReza Arabestani (International Journal of Microbiology)
Background.The iron/siderophore uptake system (IUS) involved in the Acinetobacter baumannii pathogenicity. However, IUS’s role in antibiotic resistance and the production of β-lactamase enzymes of A. baumannii are unclear. This study aimed to investigate the relationship between the production of β-lactamase enzymes and IUS regulatory genes in clinical isolates of A. baumannii. Methods. A. baumannii isolates were collected from clinical isolates using biochemical tests. The antibiotic resistance patterns and β-lactamase-producing strains were identified using the disk diffusion method (DDM). Also, IUS genes were detected by the polymerase chain reaction (PCR) method. Results. Seventy-two (72) A. baumannii isolates were collected from a different clinical specimen. Gentamicin-resistant strains (43%) had the highest frequency, and aztreonam-resistant strains (12.5%) had the lowest frequency. Also, the distribution of AmpC and MBL producing isolates were 27.7% and 35%, respectively. Moreover, the frequencies of basD, bauA, pld, paaE, entA, feoB, hemO, and tonB genes were as follows: 12.5%, 15.2%, 11.1%, 15.2%, 19.4%, 16.6%, 23.6%, and 6.9%. Further, a strong correlation was observed between the abundance of β-lactamase-producing strains and IUS genes. Conclusions. Based on our knowledge from this study, the association between β-lactamase production and IUS genes in A. baumannii plays an essential role in the emergence of drug-resistant strains.